Purification of Bioxylitol by Liquid–Liquid Extraction from Enzymatic Reaction Mixture - Low, Wai Mun; M. Rafiqul, Islam; Mimi Sakinah, A. M.; Zularisam, A. W. (Taylor & Francis, 2016)
Xylitol purification is the most difficult step of the whole manufacturing process, and its purification being of commercial importance. This study aimed to purify bioxylitol by liquid–liquid extraction (LLE) from enzymatic reaction mixture. Bioxylitol extraction was conducted under various conditions of extraction time (45–105 min), sample to solvent ratio (SSR) (1:1–1:9 v/v), and number of extraction stages (NES) (1–9 n), and the response surface method was followed to optimize the variables. Xylitol separation was markedly affected by SSR and NES. Optimum time, SSR, and NES determined were 60 min, 1:4.5 (v/v), and 5 (n), respectively. Xylitol extraction yield attained was 78.14% (w/w) at these conditions. This research reveals the feasibility of clarifying bioxylitol produced via enzymatic reduction of xylose by LLE using ethyl acetate.